Caracterização das populações de leveduras e dos parâmetros químicos em fermentações contaminadas durante a produção de cachaça em Minas Gerais - Pollyana Alves Borges da Silva (2009)
The cachaça fermentation process is directly affected by the natural occurring microbiota present in distillery environment. Some microorganism, considered contaminants, may have a negative influence in Cachaça yield and quality. The Cachaça fermentations are carry out in open vats and many materials are manipulated and transported several times before their use; so the control of contaminant microbiota is required to avoid the colonization and propagation of such microorganisms during the fermentations. Other important aspects are the water and sugar cane added to each fermentation cycle, which in the most distilleries, do not undergo any treatment, and therefore also transport microorganisms to fermentation vats. Those populations can decompose the final product; causing reduction of ethanol yield, increase volatile acidity and so affects the quality of beverage. The aim of this study was to characterize the microorganism populations involved in spoilage and/or stuck fermentations. The samples for microorganism isolation were obtained from six distilleries located Minas Gerais state. The Saccharomyces cerevisiae and non-Saccharomyces yeasts were identified and the chemical parameters total acidity, ethanol, total sugars and glycerol concentrations in the wine were measured to evaluate the characteristics of spoilage wine. The diversity of S. cerevisiae population in each vat was evaluated by mitochondrial DNA restriction analysis and killer activity was studied against the yeasts isolated from the same vat and reference yeasts to this test. Despite the spoilage, the range of microorganisms’ population counts, principally lactic acid bacteria, was similar to those found in non-contaminated fermentations reported by other works. NonSaccharomyces population was constituted by Candida akabanensis, Hanseniaspora guilliermondii, Issatchenkia orientalis, Kluyveromyces marxianus, Pichia fermentans, P. guilliermondii, P. membranifaciens, Torulaspora delbrueckii, Zygoascus hellenicus, Zygosaccharomyces bailii and Z. fermentati. Pichia membranifaciens was the second prevalent yeast species surpassed only by S. cerevisiae. Unpredictable we found higher diversity of S. cerevisiae strains in fermentations carried out by selected S. cerevisiae strains than spontaneous ones. Killer yeasts represented 34,78% of the yeast isolates. 7 The concentration of chemicals average 0,90 g/100 mL for total acidity in acetic acid; 15,43 g/L for total sugars; 824,16 mg/dL for glycerol and 3,53 oGL (%v/v) for ethanol in the 15 samples evaluated. This work approve producers practices of quantify the chemical parameters total acidity and total sugars concentrations to measure contamination levels on the microbiological phase of the Cachaça production.